2021
DOI: 10.4067/s0717-75182021000400595
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados con inadecuados depósitos de hierro en mujeres en primer trimestre de gestación

Abstract: Factores asociados con inadecuados depósitos de hierro en mujeres en primer trimestre de gestaciónFactors associated with inadequate iron stores in women in the first trimester of pregnancy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The key characteristics of the 78 included studies are summarized in Table A1 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key characteristics of the 78 included studies are summarized in Table A1 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 studies analyzed the relationship between ferritin concentration and food insecurity, with 7 finding a negative association, 1 finding a positive association, and 19 finding no association [ 23 , 24 , 25 , 31 , 34 , 35 , 36 , 42 , 47 , 48 , 53 , 54 , 55 , 56 , 57 , 58 , 63 , 65 , 67 , 72 , 76 , 78 , 79 , 82 , 83 , 85 , 94 ]. The studies that identified a negative association attributed this relationship to chronic iron deficiency in the diet [ 54 ], parents giving up iron-rich foods to their children and not getting enough iron themselves [ 54 ], increased inflammation reducing iron absorption [ 55 ], decreased access to heme sources of iron [ 76 ], decreased knowledge about iron supplementation [ 76 ], shorter inter-pregnancy interval with insufficient time to restore iron stores [ 48 ], and increased rates of parasitic infections that may reduce iron absorption [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation